Question
upstudy study bank question image url

\( \begin{aligned} 6 x-10+3 & =12 x \\ 6 x-7 & =12 x \\ \text { e. } \frac{4 x+5}{2 x+1} & =\frac{16}{5}\end{aligned} \)

Ask by Nunez Ball. in Indonesia
Jan 14,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: 1. \( x = -\frac{7}{6} \) (approximately -1.1667) 2. \( x = -\frac{7}{6} \) (approximately -1.1667) 3. \( x = \frac{3}{4} \) (0.75)

Solution

Solve the equation by following steps: - step0: Solve for \(x\): \(6x-7=12x\) - step1: Move the variable to the left side: \(6x-7-12x=0\) - step2: Subtract the terms: \(-6x-7=0\) - step3: Move the constant to the right side: \(-6x=0+7\) - step4: Remove 0: \(-6x=7\) - step5: Change the signs: \(6x=-7\) - step6: Divide both sides: \(\frac{6x}{6}=\frac{-7}{6}\) - step7: Divide the numbers: \(x=-\frac{7}{6}\) Solve the equation \( 6x-10+3=12x \). Solve the equation by following steps: - step0: Solve for \(x\): \(6x-10+3=12x\) - step1: Add the numbers: \(6x-7=12x\) - step2: Move the variable to the left side: \(6x-7-12x=0\) - step3: Subtract the terms: \(-6x-7=0\) - step4: Move the constant to the right side: \(-6x=0+7\) - step5: Remove 0: \(-6x=7\) - step6: Change the signs: \(6x=-7\) - step7: Divide both sides: \(\frac{6x}{6}=\frac{-7}{6}\) - step8: Divide the numbers: \(x=-\frac{7}{6}\) Solve the equation \( \frac{4x+5}{2x+1}=\frac{16}{5} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{4x+5}{2x+1}=\frac{16}{5}\) - step1: Find the domain: \(\frac{4x+5}{2x+1}=\frac{16}{5},x\neq -\frac{1}{2}\) - step2: Cross multiply: \(\left(4x+5\right)\times 5=\left(2x+1\right)\times 16\) - step3: Simplify the equation: \(5\left(4x+5\right)=16\left(2x+1\right)\) - step4: Calculate: \(20x+25=16\left(2x+1\right)\) - step5: Calculate: \(20x+25=32x+16\) - step6: Move the expression to the left side: \(20x+25-\left(32x+16\right)=0\) - step7: Calculate: \(-12x+9=0\) - step8: Move the constant to the right side: \(-12x=0-9\) - step9: Remove 0: \(-12x=-9\) - step10: Change the signs: \(12x=9\) - step11: Divide both sides: \(\frac{12x}{12}=\frac{9}{12}\) - step12: Divide the numbers: \(x=\frac{3}{4}\) - step13: Check if the solution is in the defined range: \(x=\frac{3}{4},x\neq -\frac{1}{2}\) - step14: Find the intersection: \(x=\frac{3}{4}\) Let's solve the given equations step by step. 1. **First Equation:** \[ 6x - 10 + 3 = 12x \] Simplifying this: \[ 6x - 7 = 12x \] Rearranging gives: \[ -7 = 12x - 6x \implies -7 = 6x \implies x = -\frac{7}{6} \] Thus, the solution for the first equation is: \[ x = -\frac{7}{6} \quad \text{or approximately } -1.1667 \] 2. **Second Equation:** \[ 6x - 7 = 12x \] Rearranging gives: \[ -7 = 12x - 6x \implies -7 = 6x \implies x = -\frac{7}{6} \] The solution for the second equation is the same: \[ x = -\frac{7}{6} \quad \text{or approximately } -1.1667 \] 3. **Third Equation:** \[ \frac{4x + 5}{2x + 1} = \frac{16}{5} \] Cross-multiplying gives: \[ 5(4x + 5) = 16(2x + 1) \] Expanding both sides: \[ 20x + 25 = 32x + 16 \] Rearranging gives: \[ 25 - 16 = 32x - 20x \implies 9 = 12x \implies x = \frac{3}{4} \] Thus, the solution for the third equation is: \[ x = \frac{3}{4} \quad \text{or } 0.75 \] ### Summary of Solutions: - For the first equation: \( x = -\frac{7}{6} \) - For the second equation: \( x = -\frac{7}{6} \) - For the third equation: \( x = \frac{3}{4} \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the first two equations, let's simplify them step by step. Starting with \( 6x - 10 + 3 = 12x \): 1. Combine like terms: \( 6x - 7 = 12x \) 2. Rearranging gives us \( -7 = 12x - 6x \), which simplifies to \( -7 = 6x \). 3. Dividing both sides by 6, we obtain \( x = -\frac{7}{6} \). For \( 6x - 7 = 12x \): 1. Rearranging gives \( -7 = 12x - 6x \), which simplifies to \( -7 = 6x \). 2. Dividing both sides by 6, we find \( x = -\frac{7}{6} \) again. Now, for the equation \( \frac{4x + 5}{2x + 1} = \frac{16}{5} \): 1. Cross-multiply: \( 5(4x + 5) = 16(2x + 1) \). 2. Expanding both sides results in \( 20x + 25 = 32x + 16 \). 3. Rearrange to get all x terms on one side: \( 25 - 16 = 32x - 20x \). 4. This simplifies to \( 9 = 12x \), or \( x = \frac{9}{12} = \frac{3}{4} \). So the solutions to the equations are \( x = -\frac{7}{6} \) for the first two and \( x = \frac{3}{4} \) for the third. Happy solving!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy